A STUDY ON PRE AND POST-MERGER FINANCIAL PERFORMANCE OF CANARA BANK - Abhi Dutt Sharma and Dr. Pradeep Kumar Garg (International journal of economic perspectives, 2022)
Mergers and acquisitions are most widely used strategy by firms to strengthen and maintain their position in the marketplace. In the present times, the banking sector is a rapidly growing industry in India. A comparatively new development in the Indian banking sector is enhanced through mergers and acquisitions. The aim of the research was to focuses on the impact of pre & post-merger financial performance of Canara bank. A comparatively new development in the Indian banking sector is enhanced through mergers and acquisitions. It permits banks to achieve a world class position and throw superior value to the stakeholders. The impact of merger on a company’s stock and the effect on the equity share of the shareholder’s capital is usually proportional. Performance of the bank pre- and post-merger usually is in the green and improved. Most findings of research state that to a certain extent M&A’s have been successful in Indian banking sector. The results conclude that merger of bank and capital infusion to banking sector leads to stability in the banking sector as well as growth of economy